140k views
1 vote
Write the expressions in standard form. SHOW ALL STEPS! The sum of 9t – 13 and the opposite of 9t.

User Rourke
by
5.0k points

1 Answer

3 votes

Answer:

-13

Explanation:

Opposite of 9t = -9t

Taking the sum of 9t - 13 and -9t

Sum = 9t - 13 + (-9t)

Sum = 9t - 13 - 9t

Sum = 9t-9t - 13

Sum = -13

Hence the expression in standard form is -13

User Travis Watson
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.